Erythropoietic protoporphyria and early onset of cholestasis - Khalili, Mani Jeh; Farahmand, Fatemeh; Hirbod-Mobarakeh, Armin; Yousefi, Azizollah; Sotoudeh, Soheila; Monajemzadeh, Maryam; Razaghian, Anahita; Rezaei, Nima (The Turkish Journal of Pediatrics, 2012)
Erythropoietic protoporphyria (EPP) is an inherited defect of mitochondrial ferrochelatase. This defect results in accumulation of protoporphyrin in erythrocytes, plasma, liver, and skin, which causes severe photosensitivity. Liver disease can occur in 1-4% of the patients with EPP, usually after at least a decade of photosensitivity. Herein, we describe a 1.5-year-old child with EPP with severe photosensitivity, heart abnormalities and early onset of cholestatic liver disease, whose clinical condition improved gradually after using ursodeoxycholic acid. It seems that liver disease in EPP patients is not limited to the late phases of the disease and could develop in childhood and early phases of EPP. Awareness among physicians has a major role in the early detection and prevention of mistreatment of EPP in case of its combination with other abnormalities.